Sensory and pain modulation profiles of ongoing central neuropathic extremity pain in multiple sclerosis - Srotova, Iva; Kocica, Jan; Vollert, Jan; Kolcava, Jan; Hulova, Monika; Jarkovsky, Jiří; Dusek, Ladislav; Bednarik, Josef; Vlckova, Eva (European journal of pain, 2021)
Background Central neuropathic extremity pain (CNEP) is the most frequent type of pain in multiple sclerosis (MS). The aim of the present study was to evaluate sensory and pain modulation profiles in MS patients with CNEP. Methods In a single-centre observational study, a group of 56 CNEP MS patients was compared with 63 pain-free MS patients and with a sex- and age-adjusted control group. Standardized quantitative sensory testing (QST) and dynamic QST (dQST) protocols comprising temporal summation and conditioned pain modulation tests were used to compare sensory profiles. Results Loss-type QST abnormalities in both thermal and mechanical QST modalities prevailed in both MS subgroups and correlated significantly with higher degree of disability expressed as Expanded Disability Status Scale (EDSS). Comparison of sensory phenotypes disclosed a higher frequency of the ‘sensory loss’ prototypic sensory phenotype in the CNEP subgroup (30%) compared with pain-free MS patients (6%; p = .003). Conclusion The role of aging process and higher lesion load in the spinothalamocortical pathway might be possible explanation for pain development in this particular ‘deafferentation’ subtype of central neuropathic pain in MS. We were unable to support the role of central sensitization or endogenous facilitatory and inhibitory mechanisms in the development of CNEP in MS. Significance This article presents higher prevalence of the ‘sensory loss’ prototypic sensory phenotype in multiple sclerosis patients with central extremity neuropathic pain compared to pain-free patients. Higher degree of disability underlines the possible role of higher lesion load in the somatosensory pathways in this particular ‘deafferentation’ type of central neuropathic pain.
First published: 10 November 2020
Gesehen am 20.07.2021